2010
DOI: 10.1074/jbc.m109.094938
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV Activity of Defective Cyanovirin-N Mutants Is Restored by Dimerization

Abstract: Cyanovirin-N (CV-N) is a two-domain, cyanobacterial protein that inhibits human immunodeficiency virus (HIV) at nanomolar concentrations by binding to high mannose sugars on the HIV envelope glycoprotein gp120. The wild type protein can exist as a monomer or a domain-swapped dimer with the monomer and dimer containing two or four sugar binding sites, respectively, one on each domain. Here we demonstrate that monomeric, single binding site mutants are completely inactive and that a single site, whether located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 39 publications
6
55
0
Order By: Relevance
“…Variants with three binding sites knocked out were unable to neutralize HIV at the concentrations tested (data not shown). These data are consistent with previously published accounts, which showed that at least two functional binding sites are required for activity (16,19), and are also consistent with the hypothesis that avidity is an important factor for viral neutralization by CV-N. Interestingly, CVN 2 L0 variants that contain one functional A and one functional B binding site did not neutralize with the same potency as WT CV-N. CVN 2 L0 ΔA∥B and CVN 2 L0 ΔA×B in which the active A and B binding sites are on the same pseudomonomer or opposite pseudomonomer (Fig. 4C), respectively, were 15-to 75-fold less potent than monomeric WT CV-N, which also contains only a single A and single B binding site.…”
Section: Cv-n Dimers Exhibit Broad Cross-clade Reactivity and Are Comsupporting
confidence: 83%
See 2 more Smart Citations
“…Variants with three binding sites knocked out were unable to neutralize HIV at the concentrations tested (data not shown). These data are consistent with previously published accounts, which showed that at least two functional binding sites are required for activity (16,19), and are also consistent with the hypothesis that avidity is an important factor for viral neutralization by CV-N. Interestingly, CVN 2 L0 variants that contain one functional A and one functional B binding site did not neutralize with the same potency as WT CV-N. CVN 2 L0 ΔA∥B and CVN 2 L0 ΔA×B in which the active A and B binding sites are on the same pseudomonomer or opposite pseudomonomer (Fig. 4C), respectively, were 15-to 75-fold less potent than monomeric WT CV-N, which also contains only a single A and single B binding site.…”
Section: Cv-n Dimers Exhibit Broad Cross-clade Reactivity and Are Comsupporting
confidence: 83%
“…These linked dimers show enhanced HIV neutralization compared to WT CV-N against 33 strains from 3 clades. In addition, we show that although two carbohydrate binding sites are sufficient for activity as previously reported (18,19), variants with more binding sites (three or four) have increased neutralization activity.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Likewise, superposition of free Cyt-CVNH (black contours) and protein in the presence of 6 molar equivalents of Man-3 or 2 molar equivalents of Man-9 (magenta) are provided in Fig. 2 In the past, attempts to structurally monitor Man-9 binding to CV-N by NMR were hampered by extreme line broadening and ultimately disappearance of resonances in the 1 H-15 N HSQC spectra, accompanied by precipitation of the sugar⅐ protein caused by multisite/multivalent cross-linking (7,19,20). In contrast to the findings with CV-N, no aggregation or precipitation was observed for Man-9 binding to Cyt-CVNH.…”
Section: Resultsmentioning
confidence: 99%
“…For CV-N, the presence of two binding sites and the multivalency of the carbohydrate have been implicated as important factors for its anti-HIV activity (6). Unfortunately, cross-linking-mediated aggregation and precipitation have hampered studies of CV-N/Man-9 interactions at the atomic level in vitro (7,19,20) and have precluded unambiguous determination of whether multivalent and multisite sugar/protein interactions are a necessary prerequisite for the antiviral activity of cyanovirin-N homolog (CVNH) proteins. However, in contrast, considerable atomic level information is available on CV-N binding to substructures of Man-8 and Man-9.…”
mentioning
confidence: 99%